Réponses

2014-04-24T10:08:01+02:00
Ex1:
1a) f(x)=4x+2
1b) B2=-4*5+2=-18
C2=4*0+2=2
D2=4*5+2=22
E2=4*10+2=42
2a) En B3 on entre =5*B1-4
2b) B3=-5*5-4=-29
C3=5*0-4=-4
D3=5*5-4=21
E3=5*10-4=46

Ex2 : incomplet

Ex3:
1) f(x)=(x+3)²-(x+3)(5-x)
f(x)=x²+6x+9-(5x-x²+15-3x)
f(x)=x²+6x+9-5x+x²-15+3x
f(x)=2x²+4x-6

2) f(x)=(x+3)²-(x+3)(5-x)
f(x)=(x+3) [(x+3)-(5-x)]
f(x)=(x+3)(x+3+x-5)
f(x)=(x+3)(2x-2)

3) f(0)=2*0+4*0-6=-6
f(-3)=(-3+3)(-2*3-2)=0*(-8)=0
f(5)=(5+3)²+(5+3)(5-5)=8²=64
f(1)=(1+3)(2-2)=0

4a)  f(-3)=f(1)=0 donc des antécédents de 0 sont -3 et 1
4b) (x+3)(2x-2)=0
⇔x+3=0 ou 2x-2=0
⇔x=-3 ou 2x=2
⇔x=-3 ou x=1

5a) f(0)=-6 donc 0 est un antécédent de -6 par f
5b) f(x)=-6
⇔2x²+4x-6=-6
⇔2x²+4x-6+6=0
⇔2x²+4x=0
5c) 2x²+4x=0
⇔x²+2x=0
⇔x(x+2)=0
⇔x=0 ou x=-2
5c) 0 et -2 sont les antécédents de -6 par f.